FATORES CAUSADORES DE ESTRESSE: UM ESTUDO DESCRITIVO COM OS OFICIAIS DE JUSTIÇA AVALIADORES FEDERAIS - MACHADO, PATRÍCIA INEZ DA SILVA (2016)
This work is linked to the concentration area Estratégia, Inovação e Tecnologia do PPGADM and to the research line Estratégia do Mestrado Profissional em Administração da Universidade Estadual do Centro-Oeste (UNICENTRO). This study had as research focus the Federal Appraiser Justice Officers associated with Assojaf MG or Assojaf PR. The general goal was to identify occupational factors that cause stress in the professional activity of the referred population. Data were collected from December 2015 to January 2016 and the research instrument used was a survey composed by questions related to the Modelo Teórico de Explicação do Estresse Ocupacional em Gerentes (MTEG) developed by Zille (2005), as well as questions contained in the study by Merlo et al. (2012). It was found that most of the sample surveyed claimed to be male, aged between 31 and 40 years, acting as Justice Officer from 11 to 20 years, postgraduated, not engaged in any other professional activity, married or in an stable relationship and allocated in the countryside of the state. In this study, were identified as occupational factors that cause stress in the professional activity the work overload factor, the professional recognition factor, the threat / aggression / violence factor, self-recognition factor and the clarity of information factor. In this sense, it was identified that the work overload factor showed the highest average in relation to other factors and may be indicated as the main factor related to occupational stress in the studied population. There was no gender-based difference in any of the factors. Regarding the place of allocation, it was found that the work overload and recognition are factors differ between the groups based on allocation. The results indicate the existence of differences between capital allocated and countryside allocated subjects, with higher averages in the case of work overload factor for capital allocated subjects and higher average in the case of professional recognition for countryside allocated subjects. It was also found that 73.9% of the sample claimed to have suffered threats / violence / verbal abuse on duty.